Effects of Autologous Conditioned Serum on Non-Union After Open Reduction Internal Fixation Failure: A Case Series and Literature Review - Pen-Gang Cheng; Man-Kuan Au; Chian-Her Lee; Meng-Jen Huang; Kuender D. Yang; Chun-Sheng Hsu; Chi-Hui Wang (Medicina)
Background and Objectives: Non-union is a severe complication of traumatic fracture that often leads to disability and decreased quality of life, with treatment remaining complex due to a lack of standardized protocols. This study examines the effectiveness of autologous conditioned serum (ACS) for non-union in patients who have a failed open reduction internal fixation (ORIF). Materials and Methods: Eleven patients with confirmed non-union at least 9 months post-ORIF or total hip replacement were enrolled. These patients received ACS treatment on the lesion sites once to three times monthly and were followed up. Efficacy was monitored through monthly X-rays to assess callus formation and bone union. Results: Seven patients received ACS three times, three patients received it twice, and the one who underwent total hip replacement received it once. Ten patients achieved union at the last follow-up visit, indicating the effectiveness of ACS in non-union cases unresponsive to ORIF. ACS demonstrated promising results in facilitating bone union in these challenging cases. Conclusions: ACS has the potential as an alternative or adjective treatment for non-union and is worthy of being investigated further for the benefits of patients.